Motivasi Berwirausaha, Self-Confidence dan Kreativitas Terhadap Minat Wirausaha - Septianti, Dian; Putri, Nyayu Khariani (Universitas muhammadiyah palembang, 2023)
The research aims to analyze the influence of entrepreneurial motivation, self-confidence, and creativity on the entrepreneurial interest of students at the Faculty of Economics and Business, Tridinanti University. Data analysis uses qualitative and quantitative methods using primary and secondary data sources. The population consists of all students from the Faculty of Economics and Business who are currently taking the Entrepreneurship Practicum course. The sampling technique is a saturated sample and a sample of 200 respondents. The research results obtained simultaneously showed a significant influence between entrepreneurial motivation, self-confidence, and creativity on entrepreneurial interest where sig. 0.000 and there is also a partial influence on entrepreneurial motivation, self-confidence, and creativity. Meanwhile, self-confidence is the most dominant variable influencing entrepreneurial interest.